2006
DOI: 10.1128/aem.72.3.2280-2282.2006
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic Microcapsules That Enhance Microbial Viability during Nonrefrigerated Storage and Gastrointestinal Transit

Abstract: A Bifidobacterium infantis strain was microencapsulated within a film-forming protein-carbohydrate-oil emulsion. This novel encapsulant incorporated prebiotics and substantially protected the bacterium during nonrefrigerated storage and gastrointestinal transit. The dried microcapsules were small (15 to 20 m), had low water activity (0.2 to 0.3), and rapidly released the bacteria in simulated intestinal fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(73 citation statements)
references
References 14 publications
6
65
0
2
Order By: Relevance
“…Development of a lyophilized synbiotic preparation containing lactobacilli and prebiotics: The freeze dried synbiotic formulation was developed on the basis of the method followed earlier by Collins and Hall (1984) and Crittenden et al (2006) with suitable modifications. The selected Lactobacillus culture was inoculated into modified MRS broth @ 2% and incubated at 37°C for 48 h under aerobic conditions.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Development of a lyophilized synbiotic preparation containing lactobacilli and prebiotics: The freeze dried synbiotic formulation was developed on the basis of the method followed earlier by Collins and Hall (1984) and Crittenden et al (2006) with suitable modifications. The selected Lactobacillus culture was inoculated into modified MRS broth @ 2% and incubated at 37°C for 48 h under aerobic conditions.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…helveticus showed better survival than free cells in the produced yoghurts during storage and during exposure to simulated gastrointestinal conditions. The use of prebiotic in the wall material was reported to improve the survival of the encapsulated probiotic (Crittenden et al 2006). A B. infantis strain was efficiently microencapsulated in a film-forming protein-carbohydrate-lipid emulsion containing canola vegetable oil, caseinate, and prebiotic fructo-oligosaccharides (FOS) plus either dried glucose syrup (DGS) or microfluidized resistant starch (RS).…”
Section: Sodium Caseinatementioning
confidence: 99%
“…The microencapsulated probiotic retained high viability during storage for 5 weeks at 25°C and relative humidity of 50%. Microscopic examination showed that the bacteria remained entrapped within the capsule material in simulated gastric fluid but were released when transferred to simulated intestinal fluid (Crittenden et al 2006). Lb.…”
Section: Sodium Caseinatementioning
confidence: 99%
“…Upon ingestion of meal gastric pH at first increases and then returns back to the fasting pH values within 3-4 hours [25]. Some of the reported protective strategies to address the pH instability are microencapsulation by enteric polymers like cellulose acetate phthalate [26], coating of probiotics with lipidic excipients like waxes [16], mixing with resistant starch [27] and symbiotic microencapsulation by emulsion spray drying technique [28].…”
Section: Aqueous Ph Stability Profile Of B Coagulansmentioning
confidence: 99%